Direct C–H alkylation and indole formation of anilines with diazo compounds under rhodium catalysis. Issue 97 (13th October 2015) - Mishra, Neeraj Kumar; Choi, Miji; Jo, Hyeim; Oh, Yongguk; Sharma, Satyasheel; Han, Sang Hoon; Jeong, Taejoo; Han, Sangil; Lee, Seok-Yong; Kim, In Su
Abstract : The rhodium(iii )-catalyzed direct functionalization of aniline C–H bonds with α-diazo compounds for the preparation of ortho -alkylated anilines and highly substituted indoles is described. Abstract : The rhodium(iii )-catalyzed direct functionalization of aniline C–H bonds with α-diazo compounds is described. These transformations provide a facile construction of ortho -alkylated anilines with diazo malonates or highly substituted indoles with diazo acetoacetates.